Analisis Ketidakefektifan Kalimat Teks Esai Berjudul Kumpulan Esai Kritis NACE Competition 2021 pada Laman LK2 FHUI sebagai Bacaan Edukasi - Lailika Adha Mundafa; Ira Fazira; Fitriana Rahmadani Irma Anggraeni; Trima Putri Nur Rahayu; Erna Hidayanti; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Muhammad Sabbardi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The use of effective sentences in academic communication is essential, especially in essay writing that contains various legal arguments. Essays should employ proper sentence structures to clearly conver ideas and persuade readers. This study aims to analyze ineffective sentence constructions found in the Kumpulan Esai Kritis NACE Competition 2021 published on thr LK2 FHUI website as educational reading material. The research method used is descriptive qualitative and theoretical. Data collection was carried out using observation and note-taking techniques by analyzing various types of errors in the essay texts. The data collection process followed four steps: (1) data collection, (2) data analysis, (3) discussion, and (4) conculusion and recommendation. The results show that many ineffective sentences are still found in the essays, such as punctuation errors, wordiness, inappropriate use of foreign terms, improper word choices, and excessive repetition. These errors negatively impact the clarity and persuasiveness of the messages and arguments within the essays. This research is expected to contribute to improving essay writing quality and the development of more effective academic literacy.